2003
DOI: 10.4040/jkan.2003.33.4.471
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Post Menopausal Women

Abstract: Purpose. This cross-sectional survey research was undertaken to examine the degree of depression in postmenopausal women and to analyze the factors affecting that depression.Method. 325 people from public health center in Inchon were surveyed as the subject of this study. Data collection was conducted through the use of questionnaires. Results.The above half of these sampled people were in depressed state (64.0%) and the mean score of depression was 12.71. There were significant differences in the depression s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…Other socioeconomic factors, such as annual income were also inversely associated with depressive symptoms in a number of studies, similar to our findings (Rajala et al, 1994;Woo et al, 1994). More specifically, in a study of postmenopausal women, significant differences in depressive symptoms were observed in relation to economic levels (Lee, 2003). Older adults living alone in our study often suffered from severe depressive symptoms.…”
Section: Other Depressive Symptoms Determinantssupporting
confidence: 91%
See 4 more Smart Citations
“…Other socioeconomic factors, such as annual income were also inversely associated with depressive symptoms in a number of studies, similar to our findings (Rajala et al, 1994;Woo et al, 1994). More specifically, in a study of postmenopausal women, significant differences in depressive symptoms were observed in relation to economic levels (Lee, 2003). Older adults living alone in our study often suffered from severe depressive symptoms.…”
Section: Other Depressive Symptoms Determinantssupporting
confidence: 91%
“…Furthermore, educated women have been reported to have a more positive reaction to menopause (Chen, Voda, & Mansfield, 1998). Smoking is among the factors known to have the strongest correlations with depressive symptoms (Lee, 2003;Wilhelm et al, 2003). In our study current smoking was also positively related with the likelihood of having severe depressive symptoms.…”
Section: Other Depressive Symptoms Determinantsmentioning
confidence: 59%
See 3 more Smart Citations